Hydraulic Analysis of Micro-irrigation Laterals: a New Approach - Mohd Soom, Mohd Amin; Svehlik, Z. J. (Universiti Putra Malaysia Press, 1994)
The current approach in hydraulic analysis of micro-irrigation laterals has been derived from sprinkler irrigation design where pipe sizes and flow rates are large. The approach assumes uniform emitter discharge and emitter barb head loss, or uses empirical formula which are not applicable to micro-irrigation systems due to errors caused by ignoring the effect of water temperature. The formula do not fit the actual head loss in small diameter polyethylene pipes for the range of Reynolds number normally encountered in micro-irrigation and should not be used for accurate analysis. The Darcy-Weisbach equation with a combined friction factor for the smooth pipe and local loss due to emitter connection used in a step by step evaluation of head loss gives more accurate results than the current method. The new approach also considers emitter manufacturing variation, and the effect of temperature changes on emitter discharge and lateral flow rates. This approach makes the use of equivalent pipe length for emitter connection head loss and a factor for dividing flow unnecessary.